The expressions of NF-kb and TGFb-1 on odontoblast-like cells of human dental pulp injected with propolis extracts - Ira Widjiastuti; Ketut Suardita; Widya Saraswati (Universitas Airlangga, 2014)
Background: Propolis is known to have beneficial effects, namely anti- bacterial, anti-viral, anti-inflammatory, antioxidant, and immunomodulatory. Propolis extracts with anti-inflammatory properties are expected to be useful in treating inflamed pulp tissue with a diagnosis of reversible pulpitis. The inflammation of pulp tissue is caused by bacteria, namely Lactobacillus acidophilus. This research used odontoblast like cells derived from pulp tissue of human third molars. Odontoblast like cells exposed to Lactobacillus achidophilus were used as a model of proinflammatory cytokine signaling. This research examined the effects of propolis extracts on odontoblast like cells exposed to Lactobacillus acidophilus. Purpose: This research was aimed to determine the effectiveness of propolis extracts on the activities of odontoblast-like cells exposed to Lactobacillus acidophillus by measuring the expressions of NFkb and TGF- b1. Methods: First, pulp odontoblast cultures were derived from human dental pulp tissues of impacted third molars removed by using digestion method. Next, odontoblast-like cells exposed to inactive Lactobacillus acidophilus bacteria were given propolis extract. Finally, the activities of odontoblast-like cells were monitored by measuring the expressions of NF-kb and TGFb-1 with immunocytochemistry technique. Results: A decline NF-kb expression and on increase of TGFb-1 expression on odontoblast like cells exposed to inactive Lactobacillus acidophilus. Conclusion: Propolis extracts inhibit the expression of NF-kb, and increase the expression of TGF-b1 in pulp odontoblast-like cells exposed to inactive Lactobacillus acidophillus. <span style="font-family: Tribune-Italic; font-size: 9pt; color: #231f20; font-style: normal; font-variant: n